Analysis of the Necessity for Steel Changing Brace Erection During the Foundation Pit Excavation in Metro Station End Shaft. Issue 1 (June 2021) - Guo, Wang; Zhao, Junyan
Abstract: Under the engineering background of end shaft construction in an underground two-story metro station, the change and development laws of supporting axial force, enclosure structural deformation and internal force during the end shaft excavation process were analyzed through the field measurement, and the measured values were statistically compared with the design values. The results indicate that it is very necessary to erect steel changing brace in the design, which exerts an unobvious effect on mitigating the enclosure structural deformation of the foundation pit in practical engineering, but apparently affects the axial force of adjacent steel braces in the steel changing brace. The results can be verified through the long-term monitoring at different points during the subsequent metro construction, and other steel changing brace forms convenient for the construction should be considered to substitute the conventional steel changing brace.